A perspective on international law - Syed Hamid Albar (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2021)
This article explores the evolution and role of contemporary international law vis-a-vis international politics. It considers how these rules and norms regulate the conduct of states and other entities in their relations, internally and externally. The article discusses the polemics between different scholars on the nature of international law and its aspects to achieving peace, justice, prosperity, and freedom for all. There are those who consider international law as ineffective due to its failure in maintaining international peace or compelling states to comply. Nonetheless, it is well-accepted and important in order to attain balance and order in the management of society and international relations. Hence, it binds state and non-state actors to take efforts to avoid conflicts which can be devastating for peace, justice, and prosperity. However, the nature of the international system is such that it has not been able to dictate politics and behaviour of states. The dilemma of the international community is how to create a more level playing field for freedom and democracy to prevail. In reality, international law today is a reflection of the development of the international society in their competition for power. The current debate is on whether it is possible to create a more just and balanced international order. Thus, international law is confronted with many challenges and impediments that need to be overcome and dealt with. In conclusion, even with the prevalence of flaws and weaknesses, international law is still a necessary means in the promotion of rule of law and governance. Any breach or breakdown of international law should not be blamed on the law itself, but rather the fault of the actors that operate the system.